CRITICAL STUDY ON THE IMPLEMENTATION OF THE PROVINCIAL ROAD LEVY COLLECTION POLICY BY THE TAMANSARI VILLAGE GOVERNMENT BASED ON GOVERNMENT REGULATION 97/2012: KAJIAN KRITIS PADA IMPLEMENTASI KEBIJAKAN PENARIKAN RETRIBUSI JALAN PROVINSI OLEH PEMERINTAH DESA TAMANSARI BERDASARKAN PERATURAN PEMERINTAH 97/2012 - Royatul Firdaus; Hary Priyanto; Erna Agustina (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
Background: The road to Ijen Geopark is one of the provincial roads that connects Banyuwangi Regency and Bondowoso Regency. The activity of collecting levies by the Tamansari Village Government on road users to Ijen Geopark which is intended to increase development in Tamansari Village has become a polemic in itself. The road to Ijen Geopark has 1 lane which has 2 lanes. Government Regulation 97/2012 explains that road fees are intended for roads that have 2 lanes, each of which has at least 2 lanes. Objective: To describe, analyze and interpret the implementation of Tamansari Village Government policy in collecting provincial road levies from road users to Ijen Geopark based on Government Regulation 97/2012. Method: Using qualitative principles according to a constructive and participatory model. Primary data comes from interviews, and secondary data comes from literature reviews and various regulations relevant to the substance of the research. Result: The levy collection program can be justified if it does not violate existing provisions and is truly beneficial for development and society. Conclusion : The wrong levy collection policy causes public dissatisfaction, causes people to have no sympathy for the government, and reduces the use of infrastructure provided by the government